Effects of ohmic heating on extraction of food-grade phytochemicals from colored potato. (December 2016) - Pereira, Ricardo N.; Rodrigues, Rui M.; Genisheva, Zlatina; Oliveira, Hélder; de Freitas, Victor; Teixeira, José A.; Vicente, António A.
Abstract: The influence of ohmic heating (OH) through the application of moderate electric fields on phytochemical compounds recovery from colored potato ( Solanum tuberosum L. var. Vitelotte) was studied. A Box–Behnken design was used to simultaneously assess the effects of operational parameters such as electric field strength, temperature and process time on the yields of anthocyanins and total phenolic recovery on pretreatment of potato samples. From the analysis of the model, electric field, temperature and time were shown to have independent and interactive effects on the values of extraction yields. Aqueous extraction of phytochemical compounds after pretreatments can be described by using a two-step model involving simultaneous washing and diffusion of the solutes from the samples. Results shows that electrical fields of low energy levels and thermal effects can be combined and optimized into a single step treatment on extraction of anthocyanins and phenolic compounds from vegetable tissues providing high recovery yields with a reduced treatment time, less energy consumption and with no utilization of organic solvents (green extraction). Highlights: Colored potato is an interesting source of bioactive compounds. Ohmic Heating and its electric fields enhance extraction of phytochemicals. Several classes of phenolic compounds can be recovered after extraction treatment. Ohmic heating extraction require a low power consumption.